2020
DOI: 10.3390/agronomy10040474
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fertilization Regime on the Crop Performance and Chemical Composition of Potato (Solanum tuberosum L.) Cultivated in Central Greece

Abstract: Potato cultivation is quite demanding in inorganic nutrients and adequate fertilization is a key factor for maximizing yield and producing tubers of high quality. In the present study, a field experiment was carried out to evaluate the effect of various forms of fertilization on crop performance and the nutritional value and chemical composition of two potato varieties (cv. Spunta and cv. Kennebec). For this purpose, five different fertilizer treatments were applied namely: control (C), standard fertilizer (T1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 81 publications
8
30
0
1
Order By: Relevance
“…Similarly to in our study, Zhang et al [86] reported that increased nitrogen availability resulted in an increase in organic acid content in spinach, while the nitrogen source may also affect organic acid content in edible greens [87,88]. Moreover, the addition of zeolite seems to have a beneficial effect on organic acid accumulation, a finding that is probably associated with the better nitrogen availability in soil after zeolite application [41,89]. Heeb et al [90] also observed significant differences in citric and malic acid content when organic and inorganic fertilizers were applied in tomato plants, while these differences accreted when the nitrogen application rates were increased.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Similarly to in our study, Zhang et al [86] reported that increased nitrogen availability resulted in an increase in organic acid content in spinach, while the nitrogen source may also affect organic acid content in edible greens [87,88]. Moreover, the addition of zeolite seems to have a beneficial effect on organic acid accumulation, a finding that is probably associated with the better nitrogen availability in soil after zeolite application [41,89]. Heeb et al [90] also observed significant differences in citric and malic acid content when organic and inorganic fertilizers were applied in tomato plants, while these differences accreted when the nitrogen application rates were increased.…”
Section: Resultssupporting
confidence: 85%
“…The fertilization regime was similar to that in a recent study published by our team where all the treatments and the used fertilizers are described in detail [41]. Briefly, five fertilizer treatments with four replications (n = 4) were implemented as follows: (i) control (C), (ii) conventional fertilizer (21-0-0, N-P-K) (CF), (iii) slow release nitrogen fertilizer 46-0-0 (SR), (iv) conventional fertilizer (21-0-0, N-P-K) + Zeolite (CFZ), and v) composted sheep manure (M).…”
Section: Plant Materials and Experimental Conditionsmentioning
confidence: 95%
See 1 more Smart Citation
“…Data show that the highest values of Cacontent in tuber were obtained with soil addition of HS with M3 fertilizers (4.47, 4.87 kgfed-1) the second values with soil addition of HS with M5 (4.21, 4.61 kgfed-1) but values low when added (M4)fertilizers with soil addition of HS (2.50, 2.75 kgfed-1)in first and second season, respectively. Table 8, demonstrated that, the highest values of Mg-content in tuber were obtained with soil addition of HS with M4 fertilizers (2.54, 2.75 kgfed-1) the second values with soil addition of HS with M5 (2.53, 2.71 kgfed-1)but values low when added M3 fertilizers with soil addition of HS (1.70, 1.86 kg fed-1) in first and second season respectively.These results are harmony with those obtained by Allison et al(2001), and Petropoulos et al(2020), who found that increasing the N supply to the crop was often associated with an increase in the concentration of Mg in leaves and stems. This may due to N facilitating Mg uptake or a consequence of N delaying canopy senescence and, thus, delaying the translocation of Mg to tubers.…”
Section: N P K Ca and Mg-content In Tuber At Harvestsupporting
confidence: 90%
“…Nitrogen is an essential macronutrient that has to be replenished with fertilizer application before and during the growing period based on the cropping schedule of farmers [27,28]. In contrast to conventional crops, several studies have indicated the low requirements of wild or semi-domesticated species in nitrogen and agrochemical inputs, which further emphasize the importance of integrating such novel/alternative species in modern farming systems aiming at sustainable production of horticultural products [9,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%